Towards a social iTV service: exploring user acceptance and changing media experience. (1st January 2011) - Oksman, Virpi; Tammela, Antti; Mäkelä, Tiina; Mitchell, Keith
In this paper, we present findings from empirical studies on enduser's attitudes towards peer-to-peer (P2P) networked TV services. This paper sheds light on the changing trends of consumers' media experience. We have gathered data with different research methods; with scenario survey and focus groups in order to understand the social aspects that people associate with their TV, viewing in their everyday lives and to discuss further on how interactive TV might change the experiences and social situations in which TV is being viewed. Our primary goal is to use the understanding of the salient factors that shape social TV experience as a basis for the design of NextShare TV, a P2P social media service, which is developed by a consortium of 20 partners across Europe.